2014
DOI: 10.3389/fpsyt.2014.00017
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Intrinsic Connectivity of Amygdala in Adults with Major Depressive Disorder

Abstract: Imaging studies of major depressive disorder (MDD) have demonstrated enhanced resting-state activity of the amygdala as well as exaggerated reactivity to negative emotional stimuli relative to healthy controls (HCs). However, the abnormalities in the intrinsic connectivity of the amygdala in MDD still remain unclear. As the resting-state activity and functional connectivity (RSFC) reflect fundamental brain processes, we compared the RSFC of the amygdala between unmedicated MDD patients and HCs. Seventy-four su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(116 citation statements)
references
References 104 publications
11
95
1
1
Order By: Relevance
“…Resting state fMRI studies also have shown that connectivity in these circuits is altered in generalized anxiety disorder (40), panic disorder (41), and depression (42). Some aspects of these neuronal circuits have also been closely connected with other neurodegenerative tauopathies, e.g., progressive supranuclear palsy, as demonstrated by Gardner et al (43) and further confirmed by direct measurement of PHF-tau accumulation with [F-18]FDDNP PET (19).…”
Section: Brain-specific Neuropathology Accumulation Measured With [F-mentioning
confidence: 85%
“…Resting state fMRI studies also have shown that connectivity in these circuits is altered in generalized anxiety disorder (40), panic disorder (41), and depression (42). Some aspects of these neuronal circuits have also been closely connected with other neurodegenerative tauopathies, e.g., progressive supranuclear palsy, as demonstrated by Gardner et al (43) and further confirmed by direct measurement of PHF-tau accumulation with [F-18]FDDNP PET (19).…”
Section: Brain-specific Neuropathology Accumulation Measured With [F-mentioning
confidence: 85%
“…The current meta-analysis extends the previous findings indicating that morphological variability in a core left lateralized cortico-limbic circuit supports NE -related behavioral and functional differences in emotional processing; specifically, the propensity to worry and to ruminate on the negative events, to form persistent associations between emotional stimuli and the reduced ability to adequately regulate emotion is associated an with an increased GM in the left amygdala/PHG, potentially supporting a sustained activation and with lower WM integrity in the left UF and reduced GM in OFC/ACC associated with lower frontal activation. In major depressive disorder one of the most consistent findings is the reduced volume of the left ACC (Drevets et al, 2008); moreover histological changes (Rajkovska et al, 1999, see below) and reduced intrinsic connectivity (Ramasubbu et al, 2014) have been reported predominantly in the left cortico-limbic network (although some inconsistencies exist in the literature). Taken together, these results suggest that NE-related structural differences in the left amygdala/PHG-OFC/ACC circuit are associated to altered emotional processing and regulatory mechanisms and play a more prominent role in the pathophysiology of depression.…”
Section: Lateralitymentioning
confidence: 94%
“…Functional magnetic resonance imaging (fMRI) has been applied to examine differential activations in certain brain regions between MDD patients and healthy controls (HC), either in the resting state or in a response to a specific task. Resting-state functional connectivity (rs-FC) studies with fMRI data have reported abnormal signal fluctuations in anterior cingulate cortex (ACC) [2], amygdala [3][4][5][6] and orbitofrontal cortex (OFC) [7,8] in MDD individuals.…”
Section: Introductionmentioning
confidence: 99%